2006
DOI: 10.3758/bf03193715
|View full text |Cite
|
Sign up to set email alerts
|

Binocular shape constancy from novel views: The role of a priori constraints

Abstract: Shape constancy refers to the fact that the percept of the shape of a given object remains constant despite changes in the shape of the retinal image. The retinal image may change because of changes in the orientation of the object, relative to the observer. Shape is usually defined by angles and by ratios of distances. According to this definition, rigid motions and size scaling do not change shape. In other words, shape is invariant under similarity transformations. A perspective transformation between the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 35 publications
4
53
1
Order By: Relevance
“…A planar 3D curve will produce a degenerate view if and only if the 3D curve projects to a straight line in the 2D image (this case is easy to detect and exclude). Preliminary experiments showed that this constraint captures some aspects of human perception of a 3D shape [6,10,24]. This observation is illustrated in Figure 13 (Figure 13a is identical to Figure 1).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A planar 3D curve will produce a degenerate view if and only if the 3D curve projects to a straight line in the 2D image (this case is easy to detect and exclude). Preliminary experiments showed that this constraint captures some aspects of human perception of a 3D shape [6,10,24]. This observation is illustrated in Figure 13 (Figure 13a is identical to Figure 1).…”
Section: Discussionsupporting
confidence: 57%
“…The model does this by applying a priori constraints to a 3D interpretation of an image of the object's contours. The a priori constraints included: mirror-symmetry of the 3D shape, planarity of its contours, maximum 3D compactness and minimum surface area of the convex hull of the 3D contours [6][7][8][9][10][11]. A 3D symmetry is a natural prior in recovering 3D shapes from 2D images.…”
Section: Introductionmentioning
confidence: 99%
“…paperclips in a sequential matching task and reported reduced viewpoint costs when stereo information about object structure was available (see also Bennett & Vuong, 2006;Lee & Saunders, 2011). Similar results were earlier found by Edelman & Bülthoff (1992) also using 'bent paperclip' and amoeba stimuli (see also Burke, 2005;Chan et al, 2006;Lee & Saunders, 2011;Rock & DeVita, 1987). However, a limitation of studies using these types of stimuli is that the results are not readily generalizable as the stimuli cannot be decomposed into parts.…”
supporting
confidence: 76%
“…This finding is consistent with the predictions of structural description models that place emphasis on the important functional role of surface depth and curvature information for the representation of 3D object shape. They challenge models that do not attribute functional significance to these kinds of image features (e.g., Bulthoff & Edelman, 1992;Chan et al, 2006;Li & Pizlo, 2011;Li, Pizlo & Steinman, 2009;Pizlo, 2008;Reisenhuber & Poggio, 1999;Serre et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Pizlo et al [10] showed that symmetry prior is more important in perceptual interpretation of 3D shapes than binocular disparity. Pizlo and Stevenson [11], and Chan et al [1] showed that human performance in shape constancy experiment is better for symmetric, than for asymmetric shapes.…”
Section: Symmetry In Human Visionmentioning
confidence: 99%